The Interactome of Palmitoyl-Protein Thioesterase 1 (PPT1) Affects Neuronal Morphology and Function - Sapir, Tamar; Segal, Michal; Grigoryan, Gayane; Hansson, Karin M.; James, Peter; Segal, Menahem; Reiner, Orly (Frontiers in Cellular Neuroscience, 2019)
Palmitoyl-Protein Thioesterase 1 (PPT1) is a depalmitoylation enzyme that is mutated in cases of Neuronal Ceroid Lipofuscinosis (NCL). The hallmarks of the disease include progressive neurodegeneration and blindness, as well as seizures. In the current study we identified high-confident PPT1-binding proteins. Pathway analysis suggested their involvement in seizures and neuronal morphology. We then proceeded to demonstrate that hippocampal neurons from Ppt1-/- mice exhibit structural deficits, and further investigated electrophysiology parameters in the hippocampi of mutant mice, both in brain slices and dissociated postnatal primary cultures. Our studies reveal new mechanistic features involved in the pathophysiology of this devastating neurodegenerative disease.